Faktor-Faktor yang Berhubungan dengan Tingkat Kepadatan Lalat pada Warung Makan di Wilayah Kecamatan Saketi 2022 - Heny Sasmita; Erma Noor Wahyuningsih; Agam Kurniawan; Siti Nur Ramdaniati; E.Egriana Handayani; Ucu Wandi Somantri; Lambang Satria Himawan (Pusat Riset dan Inovasi Nasional, 2023)
Disease vector refers to an organism that transmits pathogenic viruses, bacteria, or parasites from one host to another. The aim of this study is to identify the factors associated with the density level of flies at food stalls in the Saketi Subdistrict, Pandeglang Regency. This type of research is Analytical Survey using a Cross-Sectional Survey approach through observation. The population consists of 32 food stalls in the Saketi Subdistrict. The sampling technique used is non-probability sampling with a total sampling method. The research findings are as follows There is no relationship between the availability of clean water and the fly density level at food stalls (p=0.688; RP=0.6; 95%CI 0.531–0.864). There is no relationship between the wastewater drainage system and the fly density level at food stalls (p=0.467; RP=0.5; 95%CI 0.105–2.526). There is a relationship between toilet conditions and the fly density level at food stalls (p=0.050; RP=0.11; 95%CI 0.012–1.032). There is no relationship between dishwashing facilities and the fly density level at food stalls (p=0.128; RP=0.2; 95%CI 0.049–1.222). There is no relationship between the condition of garbage bins and the fly density level at food stalls (p=0.712; RP=1.4; 95%CI 0.321–6.493). There is a relationship between humidity and the fly density level at food stalls (p=0.021; RP=8.5; 95%CI 1.430–51.362). There is no relationship between temperature and the fly density level at food stalls (p=0.636; RP=0.6; 95%CI 0.210–4.421).